Graduate Student Library Needs at Memorial University of Newfoundland: A Case Study - Kavanagh, Victoria; Barykina, Natalia (Partnership: The Canadian Journal of Library and Information Practice and Research, 2023)
Libraries are important structures for graduate students in research-intensive universities, such as Memorial University of Newfoundland (MUN). Given the complex needs of those students, it is crucial to have an updated glimpse into what works and does not work for students. The objectives of this survey were to investigate graduate students’ awareness and use of library services and resources at MUN and to explore how important and adequate existing services and resources seemed to MUN graduate students. Fortunately, the survey findings showed favourably in terms of user satisfaction, with many of the library services and resources that were rated as very important also being rated as very satisfactory. Other findings indicated that respondents placed increased importance on access to comprehensive collections of eresources, which is not surprising given the conditions of the COVID-19 pandemic. Also found was an increased need for writing resources and literature search strategies. Overall, a recurring theme for improvement was an increased promotion of our services and resources so that we can better reach our students. The insights gained from the survey will help us target this area of improvement and direct future development of graduate-student-focused services and resources. Les bibliothèques constituent d’importantes structures pour les étudiants diplômés des universités axées sur la recherche telles l’Université Memorial de Terre-Neuve (MUN). Compte tenu des besoins complexes de ces étudiants, il est essentiel de bien comprendre ce qui fonctionne et ce qui ne fonctionne pas pour eux. Ce sondage avait comme objectifs d’examiner la connaissance et l’utilisation des services et des ressources à MUN par les étudiants diplômés et d’explorer comment importants et adéquats sont perçus les services et les ressources par ces mêmes étudiants. Heureusement, les résultats du sondage se sont révélés favorables en termes de la satisfaction des utilisateurs où plusieurs services et ressources de la bibliothèque ...